Late effect of early hypoxic disturbance in the rat heart: gender differences - Netuka, I; Szárszoi, O; Malý, J; Říha, H; Turek, D; Ostádalová, I; Ostádal, B (Physiological research, 2010)
Perinatal hypoxemia may have serious long-term effects on the adult cardiovascular system and may lead to sex-dependent changes in cardiac tolerance to acute ischemia in adult life. The aim of the study was to answer the question whether gonadectomy of the male and female rats in the early phase of ontogenetic development affects the late effect of perinatal hypoxia. Pregnant Wistar rats were placed into a normobaric hypoxic chamber (12 % O(2)) 7 days before the expected date of delivery. Newborn pups were kept in the chamber with their mothers for another 5 days after birth. After hypoxic exposure all animals were kept for 3 months in room air. Some of the pups were gonadectomized right after removal from the hypoxic chamber. Ventricular arrhythmias were assessed on isolated perfused hearts. Castration did not influence arrhythmogenesis in the adult normoxic or perinatally hypoxic female hearts. Nevertheless, the number of arrhythmias was decreased in perinatally hypoxic gonadectomized males. In conclusion, we have shown that perinatal normobaric hypoxia increased cardiac tolerance to acute ischemia in adult male rats; however, it had no late effect in females. Gonadectomy did not affect arrhythmogenesis in both normoxic and hypoxic female hearts, whereas in males significantly decreased the number of arrhythmias.
Keywords: Tachycardia, Ventricular; Orchiectomy; Aging; hypoxie; Rats; Animals, Newborn; Hypoxia; těhotenství; Time Factors; sexuální faktory; Disease Models, Animal; Rats, Wistar; mužské pohlaví; Myocardial Reperfusion Injury; Prenatal Exposure Delayed Effects; ovarektomie; novorozená zvířata; Ventricular Premature Complexes; orchiektomie; krysa rodu Rattus; věkové faktory; reperfuzní poškození myokardu; stárnutí; modely nemocí na zvířatech; ženské pohlaví; zvířata; komorové extrasystoly; Ovariectomy; Pregnancy; Sex Factors; zpožděný efekt prenatální expozice; časové faktory; Heart; Age Factors; potkani Wistar; Female; komorová tachykardie; srdce; Male; Animals